Prevalence of African swine fever virus in apparently healthy domestic pigs in Uganda - Atuhaire, David Kalenzi; Afayoa, Mathias; Ochwo, Sylvester; Mwesigwa, Savannah; Mwiine, Frank Norbert; Okuni, Julius Boniface; Mukani, William Olaho; Ojok, Lonzy (BMC veterinary research, 2013)
African swine fever (ASF) is a contagious viral disease which can cause up to 100% mortality among domestic pigs leading to serious socio-economic impact on people’s livelihoods. ASF is endemic in Uganda and there is paucity of information on the epidemiology of the disease. The major aim of this study was to determine the seroprevalence and prevalence of African swine fever virus (ASFV) in apparently healthy slaughter pigs at Wambizi slaughterhouse in Kampala city, Uganda. We also estimated the presence of ASFV antibodies and circulating viral antigens in pigs from selected districts of Uganda during targeted surveillance. We analysed 540 and 181 blood samples collected from slaughter pigs and pigs from targeted surveillance districts respectively.The prevalence of ASFV in slaughter pigs was 52.96% (95% CI, 48.75-57.14) and 11.5% (95% CI, 9.06-14.45) by ELISA and PCR respectively. In surveillance districts, the proportion of ASFV positive pigs was 53.59% (95% CI, 46.33-60.71) and 0.55% (95% CI, 0.1-3.06) by ELISA and PCR respectively.The study has found out a high seroprevalence of ASFV antibodies in apparently healthy slaughter pigs and also a high proportion of ASFV antibody seropositive pigs in surveyed districts in Uganda indicating exposure to ASFV. However, there was a lower prevalence of ASFV infection implying that there could be low virulent strains of ASFV circulating in domestic pigs in Uganda which requires further investigation.
Keywords: African swine fever virus, ELISA, PCR, Prevalence, Seropositive, Slaughter pigs, Surveillance